Research this is it! : Guidelines for designing, performing, and evaluating quantitative and qualitative research - Baarda, Ben, ....- (Groningen/Utrecht : Noordhoff Uitgevers, 2020)
Research: This is it! is a unique textbook that offers an integrated discussion of quantitative and qualitative research. The theory is easily accessible, with appealing examples taken from all kinds of studies.
Keywords: Onderzoek; Research